UNDERSTANDING BEHAVIORS AT ACADEMIC ORGANIZATIONS - Sabbagh, Haidar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The way we respond to organization and management issues is determined by the organization culture, structure, environment and context. Most people work in organizations between two extremes: Either given autonomy and trusted to deliver, or continuously monitored through the command and control system with all tasks specified. It is important to have the right model of organization behavior. An emphasis should be placed on connecting with employees. Their ideas and knowledge should be valued. Listening to their needs will repay itself and will drive them towards responsible behavior. We present here insights about higher education organizations in the Middle East, by presenting snapshots from personal experiences and observations as mini-cases to describe the behavioral patterns that arise in this academic and administrative context. We describe the dynamics of the different groups at universities and try to see how universities provide good examples of complex adaptive systems.